Mental health challenges of recent immigrants in precarious work environments — a qualitative study - Shankar, Janki; Chen, Shu-Ping; Lai, Daniel W. L.; Joseph, Shawn; Narayanan, Rhea; Suleman, Zabin; Ali, H M Ashraf; Kharat, Priyadarshini (Frontiers in Psychiatry, 2024)
Recent immigrants from racialized minority backgrounds and those who are not proficient in the local language are some of the most vulnerable members of society. Despite having postsecondary educa_onal qualifica_ons and permanent residency status, many are engaged in precarious employment. There is a scarcity of research that has explicitly focused on the work experiences and mental health challenges faced by these immigrants. Using a grounded theory approach and semi-structured face-to-face interviews, this study examined the work experiences and mental health challenges of 42 recent immigrant employees from two ci_es in Canada who were working in various industries and engaged in precarious employment. Eightyone percent of the employee par_cipants were overqualified for their jobs. Findings highlighted several ongoing mental problems that par_cipants experienced, stemming from challenging physical and psychological workplace condi_ons, nega_ve mindsets associated with their recent immigrant status, and other contextual factors and barriers. However, various coping strategies, both construc_ve and unconstruc_ve, were used to address this mental distress. The study proposes a mul_dimensional approach to address workplace condi_ons to promote good mental health for these employees. This includes preventa_ve programs for raising awareness among employers about the importance of recent immigrant employees' mental health and well-being, as well as policy and legisla_on changes to ensure the employer's commitment to crea_ng a safe and culturally friendly workplace. The approach also recommends that recent immigrant employees receive occupa_onal health and safety training, learn about Canadian workplace norms and culture, and have access to professional healthcare services.